Antedents of Employee Performance in Mining Industry IKM: Antesedent Kinerja Karyawan Pada IKM Bahan Galian Industri - Anggraini, Sherly Fitria; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the effect iof job characteristics on employee performance, to determine the effect of occupational safety and health ion employee performance, to determine the effect of job characteristics on job satisfaction, to determine the ieffect of occupational safety and health on job satisfaction, to determine the effect iof ijob isatisfaction on iperformance Employee. To find out the characteristics of work and ioccupational isafety iand ihealth iaffect iemployee performance through job satisfaction as an intervening ivariable ion iCV Berkah Sejagad. This iresearch iis a quantitative research. The source of the data iin this iresearch iis ithe iprimary idata iwhich iwas iobtained through the method of distributing questionnaires. iThe iresearch isubjects iused were iall iemployees of iCV. Blessings of the Universe, totaling i80 iemployees. iTest ithe ivalidity iof ithe idata iin ithis istudy iusing Path Analysis, Hypothesis Testing. The iresults iof ithe istudy iconcluded ithat ijob icharacteristics iaffect employee performance. iOccupational iHealth iand iSafety ihas ian ieffect ion iEmployee iPerformance. iJob icharacteristics affect job isatisfaction. iOccupational iHealth iand iSafety ihas ian ieffect ion iJob iSatisfaction. iJob iSatisfaction has an ieffect ion iEmployee iPerformance. iJob iCharacteristics, iOccupational iSafety iand iHealth affect Employee Performance iwith iJob iSatisfaction ias iIntervening iVariable ion iCV. Berkah Sejagad